Evaluation of tension-stiffening, crack spacing and crack width of geopolymer concretes. (30th January 2018) - Albitar, M.; Mohamed Ali, M.S.; Visintin, P.
Highlights: Tensile stress of concrete decreases with reducing the concrete volume. Concrete cross-section has a significant influence on the transverse tensile cracks. The tension-stiffening effect of GPC is slightly more significant than that of OPC concrete. Abstract: This paper presents the results of an experimental study on the behavior of twenty geopolymer concrete prisms tested under uniaxial tension to investigate the tension-stiffening effect on the deformation and crack width of geopolymer concretes, prepared using either fly ash-based geopolymer concrete or granulated lead smelter slag (GLSS)-based geopolymer concrete. The test parameters included concrete type, concrete prism cross-section and steel bar diameter. The results suggest that the tensile stress of concrete decreases with an increase in the reinforcement ratio due to the reduction in concrete volume. Moreover, enlarging the concrete cross-section results in postponing the transverse tensile cracks. The results also suggest that geopolymer concretes exhibit slightly more significant tension-stiffening effect than that of OPC concrete. Furthermore, it has been shown that the tension-stiffening mechanisms of geopolymer and ordinary Portland cement (OPC) concretes are in agreement, suggesting that the provisions developed for OPC concrete can be modified to predict the behavior of geopolymer concrete.